COVID-19: university education approach to the pandemic - Gutierrez Chavez, Roger Giancarlo (2022)
Mr. Editor: The always unstable university education in the country was diminished as a result of the emergency declaration, when it came into effect on March 16, 2020 (Supreme Decree No. 044-2020-PCM, 2020). The pandemic in the country directly influenced the lifestyle of the entire Peruvian population; in this case, undergraduate and graduate university students who had to adapt to a different approach in their education.